Media Channel Planning Perspectives and Frameworks: Towards Integrated Brand Communication - Belling, Cameron Keith (The IIE, 2020)
This research explored the role of media channel planning within the discipline of Integrated Brand Communication (IBC) and how the lack of integration by traditional and digital channels negatively affects the media channel plan. The study engaged with sourced media channel planning frameworks that illustrate the lack of integration and provided insight to be used in the interviewing of media channel planners. This inductive approach reviewed common themes in brand communication such as media channel planning, media strategy, media contact points and the consumer media journey. Through the review of literature an identified disconnect between how media channel planners develop traditional and digital media channel plans was identified. The importance of integrating both traditional and digital media channels within one seamless consumer media journey became the identified problem for the study. A qualitative approach was applied to explore the perceptions and insights into IBC planning and media channel planning. This was achieved by in-depth interviews of senior media channel planners from leading global media agencies, who were identified based on their experience within integrated media channel planning. The methods utilised consisted of interviews and an iterative design review process to elicit further insights into the topic. The research revealed inconsistencies in the brand voice when moving from traditional to new media contact points, this disconnect across media channels stems from a lack of integrative media channel planning that can provide integration across the consumer media journey. The research proposes a contemporary framework of media channel integration. Integration is achievable within media channel planning when it is shaped by thorough research, understanding of the target consumer profile and a fluid consumer media journey. Media channel planners have the ability to craft integrated media channel plans based on these principles.
Keywords: Digital media; Integrated brand communication; Media channel planning; Media planning; New media